نشاط القنصلیة البریطانیة في الكویت ١٩٤٥_ ١٨٨٦ (Journal of the College of Education for Women, 2019)
Incoming mail from The Arabian Gulf shifted its route to the city ofAleppo in 1755 as it was used to be sent to Kuwait instead of the city ofBasra. That route became of great importance to the East India -EnglishCompany. British government extended its influence to Muscat and thesouthern coast of the Arabian Gulf after the Maritime peace treaty (PeaceTreaty General) being signed on January 21st 1820 and its immediateaftermath of the treaties of peace with Sheiks of the region .Thereafter, Britainstarted to spread its influence to Kuwait and practice pressures on is Sheikhswho rejected to comply with the British pressures.The actual activity of the British consuls in Kuwait mainly appearedbetween the years 1886-1945 as the agents, British consuls and staff wereplaying an active role. In 1886, which was an outstanding year, were Britainconfirmed its attitude to stand by Kuwait against the Ottoman Empire. One of the most active consuls, worked in Kuwait, was Colonel Bell whowitnessed the era of Sheikh Sabah bin Jabber 1859-1866. All reports assuredthe importance of Kuwait in the fields of business, transport andcommunications as well as reports of the British Vice-Consul (Jackson), whoasserted the need to protect Kuwait and keep it away from the domination ofOttoman Empire as well as others.To compete with British consuls, Russian and German consuls wereinvolved to take part in concluding agreements with Kuwait after the formalagreement between Britain and Kuwait. Such conventions led to theannouncement of the competition with clear indication to the Frenchcompetition on consular levels. The most important activities of the Britishconsuls after the end of World War I and the end of World War II, confirmedthe active role of British diplomats in the Arabian Gulf and the role of rulers ofKuwait as well.